Olive Kitteridge - Strout, Elizabeth (New York : Random House, 2008)
At the edge of the continent, in the small town of Crosby, Maine, lives Olive Kitteridge, a retired schoolteacher who deplores the changes in her town and in the world at large but doesn't always recognize the changes in those around her.
Pharmacy -- Incoming tide -- The piano player -- A little burst -- Starving -- A different road -- Winter concert -- Tulips -- Basket of trips -- Ship in a bottle -- Security -- Criminal -- River -- A reader's guide.
Includes reader's guide (p. [273]-286).
Originally published in hardcover without the reader's guide: New York : Random House, 2008.
Keywords: Retired teachers -- Maine -- Fiction; City and town life -- Maine -- Fiction; Maine -- Fiction